Educational federalism and the quality effects of tuition fees - Alexander Kemnitz (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates how the abolishment of a ban on tuition fees affects the quality of higher education with centralized and decentralized decision making. It is shown that a marginal introduction of tuition fees fully crowds out public funds under centralization, whereas educational quality improves under decentralization. However, if the government has full discretion about the tuition fee level, centralization leads to the efficient quality, fully extracting the income gains from the graduates, while decentralization typically induces inefficiently low spending levels.
Keywords: H77; I22; D78; 330; higher education; federalism; tuition fees; Studienfinanzierung; Hochschulfinanzierung; Föderalismus; Zentralstaat; Bildungsniveau; Theorie